A functional trait approach to fen restoration analysis. Issue 4 (30th April 2013) - Hedberg, Petter; Saetre, Peter; Sundberg, Sebastian; Rydin, Håkan; Kotowski, Wiktor; Güsewell, Sabine
Abstract Questions Ecological restoration has traditionally been evaluated with analyses focused on species identities and abundances. These analyses provide no ecological explanation to why certain species change in abundance. One solution may be a functional trait analysis. We asked whether shifts in functional traits could explain vegetation changes in fens restored through tree cutting and rewetting, and how the functional traits in the restored sites compare to those of the reference site? Location Three former rich fens in east‐central Sweden. Methods Tree cutting and rewetting were applied in a factorial design, and species and abundance data were recorded for 8 yrs. Abundance data and trait data of canopy height, specific leaf area (SLA) and diaspore mass were used to calculate functional richness (FRic), functional divergence (FDiv), functional dispersion (FDis) and community‐weighted mean (CWM) of functional traits. Data were analysed in a linear mixed effect model for vascular plants and bryophytes jointly, and for vascular plants separately. Results of restoration treatments were compared to data from a reference site. Results Among vascular plants, tree cutting caused a decrease in SLA, as shade‐sensitive species increased. In accordance with the change in SLA, FDis increased. In the joint analysis, tree cutting led to increased FDis, FDiv and FRic, indicating reduced filtering caused by the removal of the shading canopy, which allowed shade‐sensitive species to establish. The comparison to the reference site shows that even after 8 yrs, the restoration treatments have higher trait diversity than the reference site, indicating that the restoration sites have a too relaxed trait filter compared to conditions in an undisturbed fen. Our interpretation is that this is primarily caused by insufficient rewetting (and increased nutrient availability) that allow species of both natural and degraded fen conditions to co‐exist, and which failed to suppress the regrowth of trees. Conclusions Analysis of functional diversity improves our understanding of the ecological mechanisms affecting restoration results, and allows comparison among regions and communities with different species composition.